Modern Approach To Diagnosis And Treatment Of Patients With Chronic Cholecystitis - Remzi Ibragimovich Suleymanov (Genius Journals, 2024)
Chronic cholecystitis is a disease characterized by inflammation of the gallbladder wall. Women suffer from this disease 3-4 times more often than men, it is most often found in people with excessive body weight, but it is not exceptionally rare in persons of asthenic physique
Keywords: cholecystitis; inflammation; gallbladder; surgical treatment